The elements of the horse bridle from the Severynivka hillfort - Shelekhan, Oleksandr; Lifantii, Oksana (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2016)
This article is devoted to horse bridle details. They are made from horn and belong to the Scythian time. Artefacts and associated materials are analysed in complex. The supposition of their local production is proposed.
Ukrainian fortresses a study of a strongholds system from the early iron age in Podolia
Keywords: Eastern Podolia; Scythian time; horse bridle; horn carving; Early Iron Age